The Function of Hedge ~to omou in verbal interaction Yuriko Koike: Analysis in Interview from NTV News Channel - Parwati Hadi Noorsanti (Journal of Pragmatics Research, 2024)
Hedges are an important linguistic feature in interpersonal communication to make communication run effectively. One of the hedges widely used in Japanese verbal interaction is ~to omou. Hedges ~to omou shows the speaker's subjectivity and the intersubjectivity that emphasizes the addressee's point of view. Intersubjectivity is related to the social function of using hedges. This article explains the social function of hedges ~to omou used by Japanese politician Yuriko Koike in an interview on the theme ‘female parliamentarians in Japan’. The analysis of the social function of hedges is carried out based on the concept proposed by Lauwereyns. Data collection was carried out using the listening and recording method, and the data were then classified and analyzed based on Lauwereyns's concept regarding the social function of a hedge. The social function of hedge ~to omou is supported by other hedges with similar functions in utterances. The results of this study indicate that in utterances containing criticism and suggestions, Hedge ~to omou tends to have the social function of politeness and solidarity. While in an utterance containing opinions